"Bounded" Empowerment: Analyzing Tensions in the Practice of Youth‐Led Participatory Research in Urban Public Schools. Issue 1 (27th February 2013) - Ozer, Emily J.; Newlan, Sami; Douglas, Laura; Hubbard, Elizabeth
Abstract: This multi‐method study examines tensions in the practice of youth‐led participatory research (YPAR) in urban high schools among 15 semester‐cohorts. Student participants in the present study were 77 ethnically diverse youth from four high schools in a major metropolitan school district. Data were gathered using systematic classroom observations, interviews with teachers and students involved in the projects, and participant observation. The two most commonly‐constrained phases of the YPAR project were issue selection and action steps. A central tension in the issue selection phase for projects enacted across multiple semester cohorts was the tension between original inquiry and "traction:" Sticking with the same topic enabled sustained building of strategic alliances and expertise for making change, but limited the incoming cohort's power to define the problem to be addressed. In further analyses, we identified processes that promoted student power despite continuity‐related constraints—teachers' framing and buy‐in strategies, "micro‐power" compensation, and alignment of students' interests with the prior cohort—as well as constraints in other phases of the projects. This study's findings regarding the promotion of youth power in the face of constraints advance the integration of theory and practice in youth‐led research and have implications for participatory research more broadly.